Fetal Myocardial Function as Assessed by N-Terminal Fragment Brain Natriuretic Protein in Premature Fetuses Exposed to Intra-amniotic Inflammation - Irani, Roxanna A.; Buhimschi, Catalin S.; Cross, Sarah N.; Zhao, Guomao; Copel, Joshua A.; Bhandari, Vineet; Buhimschi, Irina A.; Bahtiyar, Mert Ozan (American Journal of Perinatology, 2020)
Objective This study aimed to determine the relationship between fetal exposure to intra-amniotic infection/inflammation (IAI) and fetal heart ventricular function as assessed by circulatory levels of N-terminal fragment brain natriuretic protein (NT-proBNP) and the Tei index.Study Design We analyzed 70 samples of paired amniotic fluid (AF) and cord blood retrieved from mothers who delivered preterm at <34 weeks as follows: Yes-IAI (n = 36) and No-IAI (n = 34). IAI was diagnosed by amniocentesis and AF mass spectrometry. Fetal exposure to inflammation was determined through the evaluation of cord blood haptoglobin (Hp) switch-on status and level, and interleukin (IL)-6 levels by Western blotting and enzyme-linked immunosorbent assay, respectively. Fetal heart function was assessed by cord blood NT-proBNP immunoassay and fetal echocardiogram (Tei index).Results IAI was characterized by significantly higher levels of AF (p < 0.001) and umbilical cord IL-6 (p = 0.004). Cord blood Hp levels and frequency of switch-on status were higher in fetuses exposed to IAI (p < 0.001, both). Fetuses exposed to IAI did not have higher levels of NT-proBNP. Following correction for gestational age and race, neither cord blood NT-proBNP nor the Tei index was significantly different in fetuses with Hp switched-on status (p > 0.05, both).Conclusion Fetal myocardial left ventricular function does not seem to be significantly impaired in fetuses born alive due to IAI if delivery of the fetus occurs immediately following the diagnosis of IAI.
Keywords: fetal echocardiogram; BNP; inflammation; infection; cardiac